VIABILITAS BENIH CENGKEH (Eugenia aromaticum L.) PADA PEMBERIAN ZPT BERBAGAIKONSENTRASI SETELAH PENYIMPANAN - Ardiwansyah, Ardiwansyah; Adelina, Enny; Samudin, Sakka (AGROTEKBIS, 2018)
This study aims is to examine the effect of GA3 and NAA on seed viability of clove after storage. This research was conducted in two steps which the first step to evaluate seed germination used Completely Randomized Design (CRD) with one factor GA3 + NAA as a growth regulator namely;control/without growth regulator (V1), GA3 + NAA 0,025 ppm (V2), GA3 + NAA 0,050 ppm (V3) ), and a vigor test of seedling as a second steps useda randomized block design (RBD), what it was repeated four times and totallywas 12 experimental units. The results showed that a concentration 0.05 ppm of GA3 + NAA better stimulatedfor 100% seed germination, 100% maximum growth potential, 3.65 days seed germination and hypothetical vigor index 0.37.